Development of a Wearable Motion Plane Business Model for Beginner Golf Swing Training in Indonesia - Bagus Putu Agnichandra Putra; Dimas Adiyasa Hartanto; Ina Agustini Murwani (Journal Research of Social Science, Economics, and Management, 2026)
This study is motivated by the increasing number of beginner golfers in Indonesia, particularly among younger age groups, which is not accompanied by adequate access to effective and affordable training. The main challenges faced by beginners include difficulties in performing consistent golf swings and the high cost of professional coaching. Therefore, this study aims to develop a wearable device business model, “Motion Plane,” as a technology-based solution for independent training. The research employed a qualitative approach using Business Model Canvas (BMC) analysis and a survey of 81 beginner golfers. The results indicate that more than 76% of respondents show strong interest in wearable technology capable of providing real-time feedback. The Motion Plane product features a glove-based sensor integrated with an AI-powered mobile application for motion analysis and progress tracking. From a financial perspective, the investment feasibility analysis demonstrates a positive Net Present Value (NPV), an Internal Rate of Return (IRR) above the cost of capital, and a relatively short payback period across different scenarios. In conclusion, Motion Plane is an innovative and financially feasible solution with strong potential to enhance the effectiveness of beginner golf training in Indonesia.